A study on haloperidol and risperidone induced metabolic derangements in patients with newly diagnosed schizophrenia - Sivagourounadin, Kiruthika; Subbiah, Vijayalakshmi; Krishnasamy, Geetha; Rajendran, Priyadharsini (International Journal of Basic & Clinical Pharmacology, 2020)
Background: The occurrence of metabolic abnormalities in schizophrenic patients has been increased with the rampant use of second-generation antipsychotics. The aim and objective of this study is to compare the metabolic derangements induced by a typical antipsychotic: haloperidol and an atypical antipsychotic, risperidone in patients with newly diagnosed schizophrenia in a tertiary care hospital. Methods: Out of 60 newly diagnosed schizophrenic patients, 30 patients received tablet haloperidol and the remaining 30 patients received tablet risperidone orally. The anthropometric measurements like height, weight, waist circumference was measured and blood investigations like fasting blood glucose level and fasting lipid profile were taken at baseline and at the end of 3 and 6 months of drug therapy. The metabolic derangements induced by the two antipsychotics were compared and analyzed at end of 3rd and 6th month using SPSS software version 16. Results: At the end of 6th month statistically significant differences (p<0.05) were observed in weight, waist circumference, fasting blood sugar, fasting triglyceride and high-density lipoprotein level between the haloperidol and risperidone group on following the International Diabetic Federation (IDF) criteria of metabolic syndrome. Risperidone caused metabolic abnormalities in 13.3%, 4 patients whereas none of the patients in haloperidol group developed metabolic syndrome. Conclusions: Hence it is concluded that the atypical antipsychotic risperidone has been associated with an increased risk of causing metabolic abnormalities than the typical antipsychotic haloperidol. Regular and periodic monitoring of the anthropometric and metabolic parameters in schizophrenic patients on antipsychotics especially the atypical antipsychotics is mandatory to prevent further complications.